2009
DOI: 10.1021/ie901000x
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study on the Influences of Framework Charges on CO2 Uptake in Metal−Organic Frameworks

Abstract: This work involved a computational study to investigate the influences of framework charges on CO2 uptake in metal−organic frameworks (MOFs), in which a total of 20 MOFs with different topologies, pore sizes, and chemical characteristics were examined. The results showed that, at atmospheric pressure, the contribution of the framework charges is generally large, and a linear relationship with pore size was found, showing that, when the pore size is larger than 3.3 nm, the contribution becomes smaller than 10%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
56
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 32 publications
3
56
0
Order By: Relevance
“…[14][15][16] At present, many studies have been carried out on the adsorption and diffusion of pure gases in ZIFs. [8][9][10][11][12][13][14][15][16][17][18][19][20] Experimentally, for example, Yaghi and co-workers measured the adsorption isotherms of CO 2 , CO, CH 4 , N 2 , and O 2 in several ZIFs. [14][15][16] Wu et al 13 studied the H 2 adsorption sites and binding energies in ZIF-8 using a combined experimental and computational method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] At present, many studies have been carried out on the adsorption and diffusion of pure gases in ZIFs. [8][9][10][11][12][13][14][15][16][17][18][19][20] Experimentally, for example, Yaghi and co-workers measured the adsorption isotherms of CO 2 , CO, CH 4 , N 2 , and O 2 in several ZIFs. [14][15][16] Wu et al 13 studied the H 2 adsorption sites and binding energies in ZIF-8 using a combined experimental and computational method.…”
Section: Introductionmentioning
confidence: 99%
“…17 They also studied the influences of framework charges on CO 2 uptake in some ZIFs. 18 Johnson and co-workers computed the adsorption and diffusion of CO 2 , N 2 , CH 4 , and H 2 in ZIF-68 and ZIF-70 from atomistic simulations. 19 Zhou et al 20 employed grand canonical Monte Carlo (GCMC) simulations to study hydrogen adsorption in ZIF-8.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al 14 investigated the influence of framework charges on the CO 2 uptake in MOFs and demonstrated that the framework charge contribution in MOFs cannot be ignored in computational screening of MOF materials for CO 2 capture. Currently, several strategies for calculating atomic charges of the MOFs are available.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers also studied the absorption capacity of methylimidazole [15][16][17] and the adsorption capacity of methylimidazole with porous materials [18][19][20] for the carbon dioxide molecule. The potential of methylimidazole for capturing carbon dioxide molecules was reported.…”
Section: Introductionmentioning
confidence: 99%